2020
DOI: 10.1016/j.powtec.2020.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric charging of polyethylene powders: Comparison of same-material and different-material contributions to the charge build-up

Abstract: The understanding of triboelectric charging of industrially important powders can help in avoiding or controlling the particle agglomeration and wall sheeting. We developed a new experimental approach to study both samematerial particle-particle (P\ \P) and different-material particle-wall (P\ \W) charging of nascent polyethylene (PE) particles born by catalytic polymerization. We constructed a simple tribocharger consisting of a metal box divided inside into several compartments filled with the PE sample and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The particle-wall collisions typically occur between objects of different materials, a situation that can be described by models that use a difference in the material property as a driving force for the charge transfer [19]. However, inter-particle collisions often occur between particles of identical material; thus, those models cannot describe experimentally observed bipolar charging in polydispersed systems of identical material [20,21]. New mosaic-based models were proposed that can explain those experiments based on the statistical variation of properties on otherwise identical materials [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The particle-wall collisions typically occur between objects of different materials, a situation that can be described by models that use a difference in the material property as a driving force for the charge transfer [19]. However, inter-particle collisions often occur between particles of identical material; thus, those models cannot describe experimentally observed bipolar charging in polydispersed systems of identical material [20,21]. New mosaic-based models were proposed that can explain those experiments based on the statistical variation of properties on otherwise identical materials [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The output electrical energy of the TENG device is quadratically proportional to the surface charge density (σ sc ) [21,27]; therefore, more efficient tribopositive materials must be developed to considerably improve TENG performance. The widely adapted tribopositive materials that tend to easily lose electrons include polyamide (PA), polypyrrole (PPy), and polyethylene (PE) [30][31][32]. Despite the promising energy harvesting performance of synthetic polymers, in the past decades, the renewable and sustainable energy sources that can have a positive impact on the environment, have gained attention.…”
Section: Introductionmentioning
confidence: 99%
“…It could be due to difference in surface properties or the size of the particles. The latter may be contributing but may not be the sole cause since a bipolar charge distribution was observed for both the largest and smallest particles in a broad PSD (particle size diameter) experiment (Konopka et al 2020). This type of behavior could be explained using the dipole amplification model as well.…”
Section: Bipolar Charging In Experimentsmentioning
confidence: 97%
“…The charging behavior for identical particles is only one piece of the puzzle for particleparticle collisions and it may be overshadowed by the effect of many other parameters relevant to gas-solid flow systems. For example, Konopka et al (2020) performed triboelectric charging experiments with poly-dispersed polyethylene particles, where they were able to differentiate between particle-wall and particle-particle charging (Konopka et al 2020). They found that particle-wall charging resulted in unipolarly charged particles, which agrees with the particlewall charging models, but the particle-particle charging lead to a bipolar charge distribution.…”
Section: Particle-size Distribution and Bipolar Chargingmentioning
confidence: 99%
See 1 more Smart Citation